Getting the details right: optical, dielectric, and vibrational outcomes of structural phase transition in one-dimensional pyrrolidinium lead iodide and the role of defects. Issue 29 (5th July 2022) - Fedoruk, Katarzyna; Zelewski, Szymon J.; Zaręba, Jan K.; Ptak, Maciej; Mączka, Mirosław; Sieradzki, Adam
Abstract : Herein, we report the synthesis, dielectric and Raman spectroscopy, calorimetric properties, and linear and nonlinear optical behavior of a one-dimensional hybrid organic–inorganic perovskite with the pyrrolidinium cation (C4 H8 NH2 PbI3, PyrPbI3 ). Abstract : One-dimensional hybrid organic–inorganic halide perovskites have recently come under the spotlight of research due to their unique optical properties, including strong light absorption and other physicochemical characteristics relevant to energy conversion applications. Exchanging organic cations in the perovskite lattice is known to strongly affect the optical and dielectric properties of the material along with structural stability, stimulating investigations of new organic cations favoring the formation of low-dimensional phases. Herein, we report the synthesis, dielectric and Raman spectroscopy, calorimetric properties, and linear and nonlinear optical behavior of 1D hybrid organic–inorganic lead iodide with the pyrrolidinium cation (C4 H8 NH2 PbI3, PyrPbI3 ). To the best of our knowledge, our results are the first showing the phase transition (PT) in this compound, which allowed us to determine its behavior in both phases. The material undergoes a first-order structural PT at 266.0 K (262.2 K) on heating (cooling). As a result of the structural PT, an abrupt rise in the dielectric permittivity, characteristic of dielectrically switchable materials, was observed. Temperature-dependent Raman spectra showed that the mechanism of the occurring PT is mainly associated with the sudden freezing of the Pyr + cations. In addition, using independent optical methods such as photoacoustic and photothermal deflection spectroscopy, photoluminescence and third harmonic generation measurements, we determined the band gap energy of 2.6 eV. Thanks to in-depth optical measurements, we further the understanding of the photoluminescence emission origin in PyrPbI3 and question the generality of the attribution of broad band emission to self-trapped excitons.